ANALISIS PELAKSANAAN ELECTRONIC TRAFFIC LAW ENFORCEMENT DALAM UPAYA PENEGAKAN HUKUM LALU LINTAS (STUDI KASUS POLRESTABES MAKASSAR) - Siti Zubaidah; Nurwahidah Mansyur (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2019)
This study aims to determine how the implementation of E-TLE (Electronic Traffic Law Enforcement) by using CCVT in the settlement of traffic crime cases. To see the inhibiting factors and the application of the E-TLE (Electronic Traffic Law Enforcement) system in Makassar City. This research was conducted at the Polrestabes Makassar with the help of data from the South Sulawesi Police and Makassar Police Sub-Directorate for Gakkum. By using field research methods and literature. The results showed that the existence of the E-TLE program in Makassar City provided learning to the community to be more obedient to traffic rules, especially in the presence of very large facts in creating security, order, smooth traffic that can change the road marking community. The implementation of the electronic system has been well implemented by all institutions involved in the E-TLE program of the police, especially traffic, the Makassar city government, the Makassar District Attorney, Bank Rakyat Indonesia, and PT. Indonesian post.